Guided assembly of nanoparticles on electrostatically charged nanocrystalline diamond thin films - Verveniotis, Elisseos; Kromka, Alexander; Ledinský, Martin; Cermák, Jan; Rezek, Bohuslav (Nanoscale research letters, 2011)
We apply atomic force microscope for local electrostatic charging of oxygen-terminated nanocrystalline diamond (NCD) thin films deposited on silicon, to induce electrostatically driven self-assembly of colloidal alumina nanoparticles into micro-patterns. Considering possible capacitive, sp2 phase and spatial uniformity factors to charging, we employ films with sub-100 nm thickness and about 60% relative sp2 phase content, probe the spatial material uniformity by Raman and electron microscopy, and repeat experiments at various positions. We demonstrate that electrostatic potential contrast on the NCD films varies between 0.1 and 1.2 V and that the contrast of more than ±1 V (as detected by Kelvin force microscopy) is able to induce self-assembly of the nanoparticles via coulombic and polarization forces. This opens prospects for applications of diamond and its unique set of properties in self-assembly of nano-devices and nano-systems.